THE EFFECTS OF COMPLEX TRAINING ON BREASTSTROKE PERFORMANCE OF YOUNG SWIMMING ATHLETES - Kwanphet, Naruebes; Choeychom, Kongkiat (Academic Journal of Thailand National Sports University, 2024)
This study aimed to investigate and compare the effects of complex training on the breaststroke performance of young swimming athletes. The participants were 30 swimmers aged 12-14 years who were registered with the Phuket Swimming Association and participated in swimming training at the Phuket Swimming Club. They were pre-tested for their speed in the 25-meter breaststroke and randomly divided into two groups (n=15/each) by matching method. The control group was trained according to the club’s regular swimming program, while the experimental group was trained with a complex training program developed by the researcher along with the club’s regular swimming program. Data were analyzed using mean, standard deviation, t-test, and Bonferroni test. The results showed no significant difference in breaststroke performances between the experimental and control groups before training. However, statistically significant differences in breaststroke performance were found between the two groups after the fourth and eighth weeks of training at a significance level of .05. CONCLUSION: Complex training is a form of coaching that aims to develop an athlete’s performance to improve fitness related to abilities such as strength, speed, and endurance.